SINERGITAS PEMERINTAH DAERAH KABUPATEN SIAK DALAM PENGEMBANGAN KABUPATEN SIAK SEBAGAI PUSAT BUDAYA MELAYU TAHUN 2017 - Eka Wahyuni Roma Fitri; Khairul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to find out how the synergy of Siak District Government in developing siak as the center of Malay culture and to know how the implementation of synergy actors involved in developing Malay culture and who are the actors involved in the synergy. This research uses qualitative research methods with descriptive research type, which can be interpreted as problem-solving process investigated by describing the state of the research subject based on the facts that appear during the study which then continued with based on the existing theories.Siak Regency is one of the autonomous regions in Indonesia which has the authority to plan and manage its development independently, in the long-term development planning (RPJPD) of Siak Regency in 2005-2025, it has formulated the vision and mission to achieve the long-term goals. The long-term development vision of Siak Regency is as the center of Malay Culture in Indonesia that is prosperous and prosperous in 2025, in that vision there is a great determination to realize the ideals as the center of Malay Culture in Indonesia. The grand design of Malay Culture development will integrate various development sectors in realizing Siak Regency as the center of Malay Culture in Indonesia, both from the physical side (facilities and infrastructure) and from non-physical side (values, customs and other cultural products).Key words : Synergy, Government, culture, Trully Malay